2022
DOI: 10.1111/hsc.13928
|View full text |Cite
|
Sign up to set email alerts
|

Giving voice to informal caregivers of community‐dwelling older adults: A systematic review of empowerment interventions

Abstract: Taking care for older adults can place informal caregivers at risk for developing health problems. Therefore, interventions aiming to empower informal caregivers have been developed. Empowerment refers to a health promotion process including strategies to improve informal caregivers' self‐care behaviours, stress‐management and caregiving skills. In literature, empowerment‐oriented interventions often target subsamples of informal caregivers defined through the care receiver's condition. These interventions, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…How those services may interact with HCWs working alongside other practitioners is an aspect that will be discussed in the interviews where appropriate. We also acknowledge the significant number of carers, such as family and friends, who provide care [33], and are often not considered when training for HCWs is developed; and incorporate this often overlooked perspective [34] However, there are considerably greater numbers of studies focusing on family carers and their needs [35][36][37]. As such this study focuses on the provision by HCWs which does not receive as much attention.…”
Section: Study Limitationsmentioning
confidence: 99%
“…How those services may interact with HCWs working alongside other practitioners is an aspect that will be discussed in the interviews where appropriate. We also acknowledge the significant number of carers, such as family and friends, who provide care [33], and are often not considered when training for HCWs is developed; and incorporate this often overlooked perspective [34] However, there are considerably greater numbers of studies focusing on family carers and their needs [35][36][37]. As such this study focuses on the provision by HCWs which does not receive as much attention.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Baydur et al reported that a participatory training method empowered and improved the capacity of participants to change lifestyle behaviors of farmers [ 16 ]. However, to the best of our knowledge, no previous studies have estimated the effectiveness of health empowerment for the CCV health of older adults [ 29 ]. Our study results indicated that participatory methods were more effective than conventional lecture methods for empowering older farmers to improve their CCV health.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of a socially active neighbourhood has been proposed to support aging in place [ 5 ]. Remote consultations [ 6 ], empowerment of caregivers [ 7 ], lifestyle redesign [ 8 ], mobility training for those who are frail [ 9 ], early identification and management of mental health [ 10 ], community exercise programmes [ 11 ], and programmes designed following a comprehensive assessment of needs [ 12 , 13 ] have been discussed. In particular, poor mobility capacity has been identified as a potent modifiable risk factor for incident disability and the quality of life [ 14 ].…”
Section: Introductionmentioning
confidence: 99%